Soil quality standards for trace elements : derivation, implementation, and interpretation - Merrington, Graham; Schoeters, Ilse. (Boca Raton, FL : CRC Press, 2011)
"A comprehensive, practical, and state of the science overview, this book addresses the derivation of soil standards for trace elements and the implementation of these standards within regulatory and risk assessment frameworks. It provides a clear description of how to derive and implement soil quality standards for trace elements in order to assess human and environmental risks. The text covers scientific developments useful for resolving discrepancies in the setting and implementation of soil quality standards. It provides useful tips, do's and don'ts on how to deal with specific issues as variation of the natural background and how to deal with soil type dependent toxicity"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Soil chemistry